Hematopoietic stem cells can be separated from leukemic cells in a subgroup of adult acute lymphoblastic leukemia patients - Wang, Wenwen; Buß, Eike Christian; Jauch, Anna; Eckstein, Volker; Wuchter, Patrick; Ho, Anthony Dick; Lutz, Christoph (Leukemia and lymphoma, 2017)
In B-cell acute lymphoblastic leukemia (B-ALL) separation of normal hematopoietic stem cells (HSC) has so far been limited to a subgroup of patients. As aldehyde dehydrogenase (ALDH)-activity is enriched in various stem cells we investigated its value for HSC isolation in adult B-ALL. Based on ALDH-activity patients could be stratified in ALDH-numerous (≥1.9% ALDH+ cells) and ALDH-rare (<1.9% ALDH+ cells) cases. In ALDH-rare B-ALL clonal-marker negative HSC could be separated by the CD34+CD38−ALDH+ phenotype, whereas this separation was not possible in ALDH-numerous B-ALL. Functional analysis confirmed the HSC-potential of isolated cells, which were uniformly CD19-negative. However, addition of ALDH-activity further improved HSC-purity. In summary, we provide a method to separate functionally normal HSC from leukemic cells in a subgroup of B-ALL patients that can be identified prospectively. This protocol thereby facilitates comparative analyses of matched HSC and leukemic cells in order to improve our understanding of leukemia evolution.